VD_FINDINFO HC / 2009 / 372 vom 6. November 2009 - VD Tribunal cantonal (2009)
OBLIGATION D'ENTRETIEN, ENFANT, POUVOIR D'EXAMEN, CONSTATATION DES FAITS, MODIFICATIONEN GÉNÉRAL, BÉNÉFICE, BÉNÉFICE NET | 280 al. 2 CC, 286 al. 2 CC, 452 al. 2 CPC